The Potential Development of Betawi Culinary as an Ecotourism Product in Jakarta - Dhian Tyas Untari (Bina Nusantara University, 2016)
The aims of this research were to rebuild the existence of Betawi culinary. The objectives of this research were representing the values of socio-cultural of Betawi culinary, determining the aspects of supply and demand, and developing strategies to improve Betawi culinary potential as an ecotourism products. The research consists method consists of three stages. Those were representation test, market test, and arranging alternatives strategic. The results show that to improve Betawi culinary as the ecotourism products in Jakarta; it can be done with a series of strategies, classified into three classifications. Those are market penetration, market development, and product development. The result is expected to be a reference to the development of Betawi culinary ecotourismas one of the products in Jakarta.